Let's Play It! Improving First Graders' Oral and Listening Skills through Songs and Videos (2018)
ABSTRACT: This action research project aimed to explore the usefulness of implementing songs, videos and Total Physical Response (TPR) instruction to enhance oral and listening skills of first-grade students at a public school in Medellin. Data collection instruments used in this project included teacher journals, two surveys and students’ artifacts. In general, data suggest that students gained confidence to pronounce English words in class, their oral and listening skills improved significantly during the implementation, their interest and motivation on the different topics increased, and their engagement in classroom activities was enhanced.